2022
DOI: 10.3390/brainsci12121607
|View full text |Cite
|
Sign up to set email alerts
|

The Lateralization of Spatial Cognition in Table Tennis Players: Neuroplasticity in the Dominant Hemisphere

Abstract: Spatial cognition facilitates the successful completion of specific cognitive tasks through lateral processing and neuroplasticity. Long-term training in table tennis induces neural processing efficiency in the visuospatial cognitive processing cortex of athletes. However, the lateralization characteristics and neural mechanisms of visual–spatial cognitive processing in table tennis players in non-sport domains are unclear. This study utilized event-related potentials to investigate differences in the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The results of the study contribute to expanding the level of knowledge regarding how the hemispheric lateralization manifested in manual laterality and motor experience influence the manual motor skills evaluated through computer tests, between different athletes and non-athletes [52][53][54][55]. Numerous studies have focused on identifying the reaction time in performing different motor tasks in relation to manual laterality [56][57][58]. A series of studies aimed at identifying the differences between athletes and non-athletes; thus, in a study carried out on a group of football players compared to non-athletes, significant differences were identified regarding the reaction time of moving and hitting the ball [54,55,59].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study contribute to expanding the level of knowledge regarding how the hemispheric lateralization manifested in manual laterality and motor experience influence the manual motor skills evaluated through computer tests, between different athletes and non-athletes [52][53][54][55]. Numerous studies have focused on identifying the reaction time in performing different motor tasks in relation to manual laterality [56][57][58]. A series of studies aimed at identifying the differences between athletes and non-athletes; thus, in a study carried out on a group of football players compared to non-athletes, significant differences were identified regarding the reaction time of moving and hitting the ball [54,55,59].…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpreted the P3 amplitude to indicate that players may devote more attention resources to memory representations associated with badminton, which is conducive to action anticipation processing speed. In addition, Peng et al (2022) demonstrated that table tennis players had superior spatial cognitive processing and task performance than nonathletes, and that the P3 amplitude was substantially greater in the right hemisphere than the left. This suggests that the advantage of table tennis players is due to the neural activity of the right hemisphere, which is conducive to spatial location processing with attention.…”
Section: Discussionmentioning
confidence: 97%